Existence and Asymptotic Behavior of Solutions for Weighted -Laplacian Integrodifferential System Multipoint and Integral Boundary Value Problems in Half Line - Guo Yunrui (Journal of Inequalities and Applications, 2010)
Abstract This paper investigates the existence and asymptotic behavior of solutions for weighted -Laplacian integro-differential system with multipoint and integral boundary value condition in half line. When the nonlinearity term satisfies sub- growth condition or general growth condition, we give the existence of solutions via Leray-Schauder degree. Moreover, the existence of nonnegative solutions has been discussed.